Determinants Factor of Entrepreneurial Interest Among University Students - Nurjanah, Anis Rofika; Rahmawati, Ika Yustina; Tubastuvi, Naelati; Bagis, Fatmah (Jurnal Ekonomi dan Bisnis Digital, 2024)
The study aims to find out the impact of entrepreneurship education, financial literacy, self-efficiency, and love of money on the entrepreneurial interests of college students. Sampling techniques include accidental sampling and data collection through questionnaires distributed to active students who have undergone matriculation at the university. This examination uses the testing of the measurement model (outer model), the structural model (inner model), and the hypothesis for the analysis of the test. Research shows that entrepreneurship education, self-efficacy, and love of money have a positive influence on student entrepreneurial interests, whereas financial literacy has no effect on student entrepreneurial interests.